Roles and Scenario of Partly Qualified Actuaries in Insurance Companies of Nepal - Bhatt, Om Prakash; Adhikari, Hari Prasad (Nepal Journal of Mathematical Sciences, 2023)
The field of actuarial science uses mathematical and statistical techniques to evaluate financial risks in the insurance and finance industries. Actuaries are creative, curious and adaptable human resources and problem solvers, who need to possess different skills and knowledge to solve risk related problems. Partly Qualified Actuaries (PQA) is semi-professionals actuary. From analyzing the financial costs of risk and uncertainty to pricing and reserving, partly qualified actuaries are important in doing the basic to advanced actuarial tasks in these businesses. The research paper investigates on the role of partly qualified actuaries in the insurance industry in Nepal and analyzes the factors impacting the role of PQA in Nepalese insurance companies. The objective of this study is to look into the scenario and important role of Partly Qualified Actuary in the insurance companies. Descriptive and analytical research design was used in this study. The data collected through questionnaire from100 respondents was used for analysis from PQA, insurance companies' staffs, policy makers and some academicians of Nepal who are well informed about actuary. The research shows that the number of PQA is increasing in Nepal every year and they are working in different insurance companies.